Nurses’ knowledge and perceptions in initiating cardiopulmonary resuscitation (CPR): a mixed method systematic review - Zullkifli, Nurul Natasha; Mohd Ali, Noor Azizah; Thandar Aung, Khin; Mohd Mokhtar, Hanida Hani; Ahayalimudin, Nurul'Ain; Ruslan, Rusila; Mohd Noh, Hairanni (IIUM Press, 2026)
Background: Cardiopulmonary resuscitation (CPR) is a critical intervention that nurses are often the first to initiate in hospital settings. Resuscitation quality depends on nurses’ knowledge, and perceived capability or self-efficacy in executing the CPR. Despite standardised training programmes, global evidence highlights persistent gaps in knowledge and CPR competence, with implications for patient outcomes. This review aimed to synthesise evidence on nurses’ knowledge, and perceptions regarding CPR initiation in hospital settings. Methods: A mixed- method systematic review was conducted. Four major electronic databases were search from 2015 to 2025 for relevant studies. The databases were searched using Medical Subject Headings (MeSH) such as ‘CPR’, ‘resuscitation’, ‘knowledge’, ‘nurses’ perceptions and ‘cardiac arrest’. The included studies methodological quality was assessed using following Joanna Briggs Institute checklists and a narrative synthesis framework. Results: Twenty-five articles were appraised with the majority classified as moderate quality. A significant and widespread deficit in nurses' CPR knowledge and a critical gap between theoretical knowledge and practical application across diverse global settings while qualitative data highlighted the emotional strain and psychological burden experienced by nurses during resuscitation events. Additional barriers included limited institutional resources and insufficient organizational support. Triangulation of the evidence confirmed four consistent themes: persistent knowledge-practice gaps, the emotional and psychological impact on nurses, the efficacy of specific training models, and the influence of systemic and environmental barriers. Conclusion: Improving resuscitation effectiveness and sustainability demands continuous, evidence-based education to prevent skill decay while addressing systemic issues through strong organizational support and integrated psychological care.